EFFECTIVENESS OF ASYNCHRONOUS DISTANCE LEARNING AMIDST THE NEW NORMAL - DR. FROILAN D. MOBO (Research Parks Publishing LLC, 2020)
The opening of classes in the tertiary level has just started and the new system has put into places like using the flexible learning set by the Commission on Higher Education. Most of the Higher Education right now are using Google Education in their teaching and learning activities like utilizing Google Classroom, Google Meet, Google Calendar, and Google Forms in replacement to the traditional face to face teaching. The Commission on Higher Education mandates the Higher Education Institutions to use online learning this is to prevent from the deadly pandemic COVID-19 being infected and to safeguard the health of our children and relatives. One of the most traditional methodology in teaching is Asynchronous Distance Learning but this not new anymore it has been existing for so long and it was only being use right now because of the current pandemic situation. One of the advantages of using Asynchronous Distance Learning is by conducting real-time online classes using the above applications in which you can interact with your students through live discussions using google meet then giving them the assessment online using google forms. The effectiveness of using the Google Apps is really effective because all the activities are being done online and yet can validate your records online and then can conduct online like conducting classes using google meet, setting calendars as schedule which will redirect to the google meet class and can also give assessment online with a feedback. With this kind of new learning approach using Asynchronous Distance Learning, the students would be able to learn while they are on their own respective homes.